An Overview of Software Architecture Education - Oliveira, Brauner R. N.; Garcés, Lina; Lyra, Kamila T.; Santos, Daniel S.; Isotani, Seiji; Nakagawa, Elisa Y. (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2022)
Software architecture comprises the most relevant structure of a software system and is a factor to enable systems to achieve qualities that are crucial to the system's goals. In this sense, teaching software architecture to students and professionals remains a very important task. However, it is still a challenging matter for teachers and learners on different levels and contexts. We also lack an updated overview on how such a challenge has been addressed. This paper presents an overview of software architecture education experiences and initiatives. For this, we systematically examined the most relevant studies addressing software architecture education. After analyzing a total of 50 studies, we discuss how software architecture has been taught, the topic mostly taught, the learning objectives, and the learning methods. Based on our findings, we also present open issues that still remain to be further investigated, aiming to mature software architecture education.